PKM Pembuatan Kemasan, Peningkatan Produksi Dan Perluasan Pemasaran Keripik Singkong Di Desa Cot Keutapang Bireuen - Rahmi; Sufritayati; Nelly; Sutoyo; Mulyadi; Safri, Hayanuddin; M Yusuf; Nurhayati, Agustina (Universitas Mataram, 2023)
In an innovation business, increasing production and marketing is very important in the progress of a company. Micro, Small and Medium Enterprises (MSMEs) are the most strategic sector of the national economy and concern the livelihoods of many people, making them the backbone of the national economy. However, the problem currently faced by small businesses or industries is industrial management and marketing. With community service related to assisting MSMEs in the traditional type of cassava chips food, it is hoped that it can provide a solution in improving the welfare of MSMEs. The problem solving method used is based on a management approach in increasing production results and sales results with 4 (four) stages of program implementation, namely preparation, implementation, monitoring and evaluation and reporting. The community service program carried out is through packaging innovation in accordance with the regulations of the Bireuen City Health Service, increasing production with a management approach and expanding marketing on social media and modern markets.